Ageing with cerebral palsy; what are the health experiences of adults with cerebral palsy? A qualitative study. Issue 10 (13th October 2016) - Mudge, Suzie; Rosie, Juliet; Stott, Susan; Taylor, Denise; Signal, Nada; McPherson, Kathryn
Abstract : Objective: To enhance understanding of the experiences of ageing with cerebral palsy (CP) in adulthood with a particular focus on experiences with health services. Design: A qualitative descriptive methodology was applied to capture adults' views of ageing with CP and related interactions with health services. Semistructured interviews were undertaken with data systematically coded and interpreted by grouping information into categories. Themes that encompassed the categories were identified through thematic analysis. Setting: All healthcare settings. Participants: 28 adults (14 women) with CP, aged 37–70 years. Results: 5 themes covered the breadth of participants' experiences: (1) acceptance of change; (2) exploring identity: cerebral palsy as only one part of self; (3) taking charge of help; (4) rethinking the future and (5) interacting with health professionals. Being seen and being heard were the features described in positive healthcare interactions. Participants also valued health professionals who reflected on who holds the knowledge?; demonstrated a willingness to learn and respected participants' knowledge and experience. Conclusions: Our findings could, and arguably should, inform more responsive strategies for disabled people in health services and, indeed, all health consumers. Our study supports other findings that impairments related to CP change and, for many, severity of disabling impact increases with age. Increased interactions with health and rehabilitation professionals, as a consequence of these changes, have the potential to impact the person's healthcare experience either positively or negatively. A 'listening health professional' may bridge their knowledge gap and, in recognising the person's own expertise, may achieve three things: a more contextualised healthcare intervention; a better healthcare experience for the person with CP and positive impact on the person's sense of autonomy and identity by recognising their expertise. Future research should identify whether this approach improves the healthcare experience for adults living with CP.